2021
DOI: 10.1111/1440-1681.13478
|View full text |Cite
|
Sign up to set email alerts
|

Delayed blockage of prostaglandin EP4 receptors can reduce dedifferentiation, epithelial‐to‐mesenchymal transition and fibrosis following acute kidney injury

Abstract: Dedifferentiation of tubular epithelial cells is involved in both regeneration and fibrosis following acute kidney injury (AKI). Prostaglandin E2 receptor 4 (EP4) antagonist can inhibit the dedifferentiation of renal tubular cells. The present study investigated whether the time of blockage of EP4 receptors, using grapiprant, could affect the tubular regeneration or interstitial fibrosis in AKI. Cisplatin was used to induce AKI in 72 C57BL/6 adult female mice. Animals were assigned to four groups; control, cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…To explore the potential role of EP receptors in the procedure of AKI-to-CKD transition, we first screened the expressions of the four G-protein-coupled receptors EP receptors in mouse kidney tissues at 2 and 14 days after IRI though single nucleus RNA sequencing (snRNA-Seq) acquired from GEO datasets (GSE139107) (Figure 1A). Although both EP3 and EP4 were highly expressed in the kidney (Figure 1B), previous studies have confirmed that EP3 was not significantly altered in the kidney of AKI mice (Abouelkheir et al, 2021). Therefore, we focused on EP4 in subsequent experiments.…”
Section: Ep4 Was Selectively Activated In Renal Macrophages After Isc...mentioning
confidence: 92%
“…To explore the potential role of EP receptors in the procedure of AKI-to-CKD transition, we first screened the expressions of the four G-protein-coupled receptors EP receptors in mouse kidney tissues at 2 and 14 days after IRI though single nucleus RNA sequencing (snRNA-Seq) acquired from GEO datasets (GSE139107) (Figure 1A). Although both EP3 and EP4 were highly expressed in the kidney (Figure 1B), previous studies have confirmed that EP3 was not significantly altered in the kidney of AKI mice (Abouelkheir et al, 2021). Therefore, we focused on EP4 in subsequent experiments.…”
Section: Ep4 Was Selectively Activated In Renal Macrophages After Isc...mentioning
confidence: 92%
“…The beneficial effect of EP4 receptor blockade was also seen in a mouse model of cisplatin-induced kidney damage. In these mice, treatment with the EP4 antagonist grapiprant, a nonsteroidal anti-inflammatory drug widely used in veterinary medicine [ 79 ], markedly reduced collagen deposition and α-smooth muscle actin expression associated with cisplatin exposure [ 80 ]. Taken together, the EP4 receptor has been the greatest focus of research to develop new renal fibrosis therapies.…”
Section: The Role Of Prostaglandin E2 Ep Receptors In Development And...mentioning
confidence: 99%
“…EMT transforms epithelial cells into myofibroblasts; these myofibroblasts proliferate and produce a fibrotic matrix [ 58 ]. A prostaglandin E-2 receptor 4 (EP4) antagonist can inhibit the de-differentiation of renal tubular cells, which targets EMT [ 59 ]. Conversely, cells in acute senescence can undergo cellular reprogramming to de-differentiate, proliferate, and differentiate to achieve tissue regeneration and repair in AKI.…”
Section: Cellular Reprogrammingmentioning
confidence: 99%